World food problems and prospects - Johnson, D. Gale (Washington : American Enterprise Institute for Public Policy Research, 1975)
The book examines the causes of the large increase in food prices in 1973-74 and of the shortfalls in food supplies in several low income countries.
Includes bibliographical references.
usc 14/02/2019
Loans
Keywords: Food supply; Food prices